REFORM OF THE INHERITANCE LAW IN THE SWISS CONFEDERATION (Reform Phase I) - Stojanovic, Natasa (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
In this paper, the author sheds light on the 2020 reform of the Swiss inheritance law, the implementation of which started in January 2023. The research was conducted with the aim of determining the scope and quality of the implemented reform of Swiss inheritance regulations. The author’s attention is focused to the solutions dedicated to: reduction in the forced heirship portion of the testator’s descendants; abolition of the forced heirship portion to his/her parents; loss of the forced heirship portion for his/her spouse/same sex partner in a registered partnership - once divorce proceedings begin, i.e. the process of dissolving a registered partnership begins, and when, prior to the ending thereof, one of the spouses/registered partners dies; one qualitatively different concept of contractual freedom through inheritance contracts; the effect that the “three pillar system” of the Swiss pension and disability insurance has upon the effectuation and protection of the right to forced heirship portion; as well as the changes and the legal and technical improvements of regulations concerning the order of charitable donations out of which a violated forced heirship portion is settled. For the purpose of this paper, the following methods are used: legal-dogmatic, normative-legal and historical-legal. According to the author’s understanding, most of the amendments to the Civil Code of the Swiss Confederation in 2020, which concern the institution of inheritance, are in the service of greater testamentary freedom of individuals with charitable donations, both inter vivos and mortis causa. However, they do not follow the social conditions in contemporary Switzerland sufficiently, since the right of inheritance is not recognised by law to a non-marital partner, as is the case with a spouse or a same-sex partner from a registered partnership, although a non-marital partnership exists parallel to marriage and a registered same-sex partnership.